Histomorphological spectrum of central nervous system lesions in a tertiary care hospital - Shah, Hetal Kirit; Dongre, Suryakant; Karle, Ravindra (International Journal of Research in Medical Sciences, 2021)
Background: Central nervous system (CNS) lesions show considerable geographic and racial variations with respect to the incidence and their pattern of distribution. CNS neoplasm account for 2% of all cancers. There has been a rapid increase in incidence of CNS tumors. Many non-neoplastic CNS lesions can clinically and radiologically mimic brain tumors and to differentiate them histopathological examination is necessary. Methods: This was a descriptive cross-sectional study of 30 cases, carried out from March 2020 to February 2021, in a tertiary health care hospital. The cases were diagnosed histopathologically and categorized according to the WHO 2021 classiﬁcation. Results: The study included 30 cases. 3 (10%) of them were non-neoplastic while 27 (90%) were neoplastic with glioblastoma and diffuse astrocytoma being the most common. Overall, tumors of neuroepithelial tissue (60%) was the most common entity. Frontal lobe was the most commonly observed site in the neoplastic lesion. Headache was the most common presentation. Age range varied from 7 years to 66 years with the mean age of 32.7 years. Conclusions: The spectrum of neoplastic lesions were astrocytoma, glioblastoma, ependymoma, hemagioblastoma, medulloblastoma, meningioma, non-hodgkins lymphoma, oligodendroglioma, pitutary adenoma, schwannoma and non-neoplastic were A-V malformation, brain abscess, subdural empyema.